BIOTIC CRISES AND STAGES OF RADIOLARIAN EVOLUTION IN THE PHANEROZOIC - Afanasieva M.S.; Amon E.O. (My University, 2006)
The questions of ecology and taphonomy of radiolarians are reviewed and reexamined. In Recent oceans and seas, the major part of the “radiolarian rain” (dead individuals) comes from the layer of the water column which is not deeper than 500 m; therefore, the bottom radiolarian thanatocenoses and taphocenoses are formed in all oceanic zones, including the coastal and central oligotrophic regions of oceans. However, radiolarians should not be regarded as indicators of exclusively deepwater oceanic conditions. The crucial moments in the evolution of radiolarians at the major Phanerozoic boundaries are recognized. A dynamic model of cyclic development of radiolarians in the Phanerozoic is proposed and four phases and nine stages in their evolution are recognized. The absence of an outburst of radiolarian biodiversity in the Holocene is shown. Many great extinctions of radiolarians occurred at the boundaries between seasons of galactic years.